Development and Validation of Stereoselective Method for the Quantification of Stereoisomers of Eliglustat Using Amylose-Based Immobilized Chiral Stationary Phase - Srinivasu, Gunnam (Asian Journal of Pharmaceutics (AJP), 2021)
Aim: The main aim of the present work is to develop and validate a new simpler, selective, specific, and robust high performance liquid chromatographic method for the separation of Eliglustat and its isomers. Materials and Methods: For the accurate quantification method, for the all isomers was developed by performing the significant number of methods on trial and error techniques using a large number of polar and non-polar solvent mixtures as mobile phase. A distinctive resolution between Eliglustat and its stereo isomers was achieved on Immobilized Amylose tris (3-chloro-4-methylphenylcarbamate) stationary phase namely CHIRALPAK IF-3(4.6 mm × 250 mm, 3 μm), with flow rate of 1.0 mL/min using isocratic method containing n-Hexane/Ethanol/Methanol/ Diethyl amine (90/05/05/0.1,v/v/v/v). Column temperature was maintained at 40°C and detection wavelength of 280 nm. Results and Discussion: The limit of detection and limit of quantification values of Eliglustat S,SIsomer, R,S-Isomer, and S,R-Isomers were found to be 0.0027/0.0082, 0.0367/0.1112, and 0.0375/0.1137 μg/mL, respectively. The method was found to be precise, accurate, and linear (R2 > 0.999). Recoveries of all isomers were found to be in the range of 90–110%. Conclusion: As per the ICH guidelines, the developed method has been shown to be linear, accurate, precise, robust, and sensitive. The method is also considered quality control friendly as it is robust, uses isocratic mobile phase and employs commonly used solvents as mobile phase.